Turismo sostenible en la Reserva Nacional Allpahuayo Mishana, Loreto-Perú 2022 - Garcia Vilchez, Magaly (2023)
From January 2022 to March 2023, an investigation was carried out in the Allpahuayo National Reserve with the main objective of proposing the implementation of Sustainable Tourism, for this it was necessary to make field observations and verify the supply of plants and animal species for tourism purposes as well as the populations settled in its area of direct influence, interviews with residents and and tour operators of the city of Iquitos City, after the data analysis it is concluded that is possible to offer a Sustainable tourism of nine sub types that are offered in the world. For this, a series of previous activities is proposed, the opening of new trails, the appropriate places for each subtype of tourism also the infrastructure requirements, th necessary training for all the groups involved to it competitive at an international level.